Prevalence of early childhood caries in 3- to 5-year-old preschool children in Rohtak City, Haryana - Mamta Ghanghas; Adarsh Kumar; B C Manjunath; Ridhi Narang; Ankita Goyal; Hansa Kundu (Wolters Kluwer Medknow Publications, 2017)
Introduction: Early childhood caries (ECC) is a significant dental public health problem that affects infants and preschool children all over the world, and there is scarcity of epidemiological data regarding ECC in Rohtak city. Aim: This study aims to assess the prevalence of ECC among 3- to 5-year-old preschool children in Rohtak city, Haryana, India. Materials and Methods: A descriptive cross-sectional study was carried out among 489 preschool children aged 3-5 years in Rohtak city, Haryana. Children were randomly selected from preschools of Rohtak. Caries experience was recorded using "deft" index, and questionnaire comprising sociodemographic details and oral hygiene practices was also used. Data were analyzed using Statistical Package for Social Sciences version 20.0. Chi-square tests were used for the comparison of proportions. P < 0.05 was considered as statistically significant. Results: The overall prevalence of ECC was found to be 32% with mean deft 1.08 ± 2.27. No significant association of dental caries was found with sociodemographic factors such as gender, parental education, parental occupation, socioeconomic status, number of children, birth order, type of family, and oral hygiene practices. Conclusion: As burden of dental caries is high, treatment of dental caries would impose a great financial burden; hence, effective preventive strategies should be developed and implemented.